Development of ex vivo normothermic perfusion as an innovative method to assess pancreases after preservation - Ogbemudia, Ann (Journal of the Nuffield Department of Surgical Sciences, 2021)
Ann Ogbemudia, Julien Branchereau (Joint first authors), Gabriella Hakim, Fungai Dengu, Faysal El-Gilani, John Mulvey, Kaithlyn Rozenberg, Thomas Prudhomme, Letizia Lo Faro, James Hunter, Paul Johnson, Rutger Ploeg and Peter Friend Objective Static cold storage (SCS) is the standard method for pancreas preservation but does not facilitate objective organ assessment prior to transplantation. Normothermic machine perfusion (NMP) has been used to test other abdominal and thoracic organs’ function and viability in transplantation settings. Our aim was to develop a NMP protocol specific for pancreases and then investigate its potential as an organ assessment strategy. Method 8 porcine pancreases were procured in conditions replicating donation after circulatory death with warm ischaemia time of 25 minutes. After 3 hours of static cold storage (SCS) the pancreases were divided into 3 experimental groups 1) the feasibility group (n=2) that underwent 2.5 hours of NMP 2) the SCS group (n = 2) that underwent an additional 6 hours of SCS prior to assessment on NMP for an hour and 3) the Oxygenated Hypothermic Machine Perfusion (oxyHMP) group (n = 4) that underwent 6 hours of oxyHMP followed by 1-hour assessment on NMP. The NMP protocol used autologous, leucodepleted blood delivered at a mean arterial pressure of 40mmHg with a temperature of 37oC. At timed intervals during NMP, perfusate samples were collected for gas analysis and perfusion parameters were recorded. Results The feasibility group was used to develop the NMP protocol and demonstrated stable perfusion parameters throughout NMP. Compared to the SCS group the oxyHMP group demonstrated better average perfusion characteristics with lower resistances, higher flow rates, lower mean lactate levels and physiological pH. The oxyHMP group maintained normal macroscopic appearances during NMP. At the end of NMP the SCS group had an average 32% weight increase compared to the oxyHMP group that were found to have a 17% weight reduction. Conclusion Normothermic machine perfusion of whole pancreases is feasible after cold preservation and potentially useful as an assessment strategy. Furthermore, it demonstrated that oxygenated HMP may be beneficial for pancreas preservation compared to SCS.